Scapular position and orientation in throwing athletes - Myers, J. B.; Laudner, K. G.; Pasquale, M. R.; Bradley, J. P.; Lephart, S. M. (The American Journal of Sports Medicine, 2005)
Background: Despite the recognized importance of proper 3-dimensional motion of the scapula in throwers, minimal research has quantified scapular position and orientation in throwing athletes.